UJI COBA PROGRAM KEMITRAAN KEHUTANAN DI KESATUAN PENGELOLAAN HUTAN UNIT XIV GEDONG WANI, PROVINSI LAMPUNG Trial of Forestry Patnership Program in Forest Management Unit XIV Gedong Wani, Lampung Province - M. Saipurrozi; Indra Gumay Febryano; Hari Kaskoyo; Christine Wulandari (Lambung Mangkurat University-Indonesia, 2018)
The partnership program is one solution in conflict resolution on state forest land use by the commUnity. The aim of research to explain the trials of forestry partnership program in Forest Management Unit XIV Gedong Wani. The research approach was conducted qualitatively, where in-depth interviews, participant observation, focus group discussion and document study were conducted for data collection. The results showed that there are two forms of partnership trial that developed, where is a partnership with Agroforests Park and poultry farm group. The supporting factors of implementation of the partnership between KPH Unit XIV Gedong Wani and KTH Agroforests Park were stakeholder involvement and a high level of members trust to the management; while the inhibiting factor were their members obey the rules and interventions by NGOs Manunggal Wana Bakti against management. The supporting factors of implementation of the partnership between KPH Unit XIV Gedong Wani and poultry farm group were the involvement of the association of poultry farm entrepreneurs and the awareness level of poultry farm; while the inhibiting factor were limitations of informations, officers, and the effort by Forest Management Unit XIV Gedong Wani. Coaching and mentoring efforts should be undertaken by officers with special expertise in their fields; so it is expected to increase the capacity of the commUnity.Keywords: farmers group; forestry partnerships; Forest Management Unit (KPH); conflict; access Program kemitraan merupakan salah satu solusi dalam penyelesaian konflik pemanfaatan lahan hutan negara oleh masyarakat. Tujuan penelitian untuk menjelaskan uji coba program kemitraan kehutanan di Kesatuan Pengelolaan Hutan Unit XIV Gedong Wani. Pendekatan penelitian dilakukan secara kualitatif, dimana wawancara mendalam, observasi partisipan, focus group discussion dan studi dokumen dalam pengumpulan datanya. Hasil penelitian menunjukkan bahwa terdapat dua bentuk uji coba kemitraan yang dikembangkan yaitu kemitraan dengan kelompok tani hutan Agroforest Park dan peternak ayam. Faktor pendukung pelaksanaan uji coba kemitraan antara KPH Unit XIV Gedong Wani dan KTH Agroforest Park adalah adanya keterlibatan stakeholder terkait dan tingginya tingkat kepercayaan anggota terhadap pengurus; sementara faktor penghambatnya adalah adanya anggota yang tidak patuh terhadap aturan dan intervensi oleh LSM Manunggal Wana Bakti terhadap pengurus. Faktor pendukung uji coba kemitraan antara KPH Unit XIV Gedong Wani dan peternak ayam adalah adanya keterlibatan asosiasi pengusaha industri ayam ras dan tingkat kesadaran peternak; sedangkan faktor penghambatnya adalah keterbatasan informasi, petugas serta upaya yang dilakukan pihak KPH Unit XIV Gedong Wani. Upaya pembinaan dan pendampingan perlu dilakukan oleh petugas yang memiliki keahlian khusus dalam bidangnya; sehingga diharapkan mampu meningkatkan kapasitas masyarakat.Kata kunci: kelompok tani, kemitraan kehutanan, Kesatuan Pengelolaan Hutan (KPH), konflik, akses